The English-speaking Catholic Population Profile in Quebec, 2001 : Comparative Analysis of the Demographic Characteristics and Geographic Distribution of the FOLS-English Catholic Population in Quebec - Ahmadzadeh, Nazanin (English Speaking Catholic Council, 2004)
The general objective of this study is to provide the English-Speaking Catholic Council in Québec with a comprehensive demographic portrait of the English speaking Catholic Community in Québec. This portrait will serve as support for the orientation of the ESCC. This study follows a previous study carried out in 1992 which focused only on the parishes in the Montreal metropolitan area.

Report from the Executive Director - Hook, Deborah (Quebec Community Groups Network (QCGN), 2004)

QCGN President's Report 2003-2004 - Murphy, Martin P. (Quebec Community Groups Network (QCGN), 2004)
The Quebec Community Groups Network (QCGN) has been in existence on a formal basis since 1995. Much has been accomplished in these past nine years. Looking to the future, there are many challenges which require our attention, strong leadership and innovative ideas to enrich our identity and resolve. It is imperative that the QCGN conrinue to buiid its credibility as a strong and unhesitating voice of reason in working to enhance the development of the English-speaking minority population in Quebec.

The English-Speaking Catholic Population in Quebec, 2001 - Ahmadzadeh, Nazanin; Warnke, Jan (2004)

Respect Minority and Community Rights in Any Health Care Reforms - The English Speaking Catholic Council (ESCC) (2004)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Baseline Data Report 2003-2004 : Regional Profiles of English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2004)
This report includes a general overview of the situation of the English‐speaking population in a minority context as well as the particular demographic characteristics and vitality issues which vary tremendously across its 16 administrative health regions • The profile of each region is organized to highlight a broad range of factors that have been shown to have a strong influence on the health status of a population and ultimately the quality of life of its constituents • These health determinants are located in the context of national, provincial and regional demographic characteristics with comparisons between Anglophone minority and Francophone majority populations within a regional territory • Where significant, and possible, the tendencies of certain factors over time will be underlined • The commonalities among English‐speaking regional communities as well as the distinct features of each in terms of demographics, experiences, and attitudes are highlighted throughout this process and summarized in terms of key strengths and needs to be targeted in considering future health and social service initiatives
Keywords: Official Language Minority Community (OLMC)

Choices through Knowledge: Community training in palliative care - Jones, Jo-Ann; Quebec Association for Adult Learning (QAAL) (2004)

Community NetLink - Community Health and Social Services Network (CHSSN) (2004)

The English-speaking Catholic Population Profile in Quebec, 2001 - English Speaking Catholic Council (2004)

Going Forward : The Evolution of Quebec's English-Speaking Community - Jedwab, Jack (Canada. Office of the Comissioner of Official Languages, 2004)
This report characterizes, in the most detailed presentation to date, the Quebec Anglophone population and its evolution over time. It speaks to the community’s residential patterns, mobility, diversity and institutional characteristics. Employing a rich body of demographic, statistical and attitudinal data from census and other sources, it provides a portrait of the Anglophone population at the turn of the new century that aids a wider understanding of the community. The study also focusses on how Quebec’s English speakers perceive their current priorities and vision of the future.
Keywords: Official Language Minority Community (OLMC)

The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)